MicroRNA‐335‐5p and ‐3p synergize to inhibit estrogen receptor alpha expression and promote tamoxifen resistance. Issue 2 (12th January 2017) - Martin, Elizabeth C.; Conger, Adrienne K.; Yan, Thomas J.; Hoang, Van T.; Miller, David F. B.; Buechlein, Aaron; Rusch, Douglas B.; Nephew, Kenneth P.; Collins‐Burow, Bridgette M.; Burow, Matthew E.
Abstract : microRNAs (miRNAs) are small noncoding RNA molecules involved in the regulation of gene expression and play critical roles in human malignancies. Next‐generation sequencing analysis of the MCF‐7 breast cancer cell line overexpressing miR‐335‐5p and miR‐335‐3p demonstrated that the miRNA duplex repressed genes involved in the ERα signaling pathway, and enhanced resistance of MCF‐7 cells to the growth inhibitory effects of tamoxifen. These data suggest that despite its conventional role in tumor suppression, the miR‐335 transcript can also play an oncogenic role in promoting agonistic estrogen signaling in a cancerous setting. Abstract :